Capping of a surface slurried coal tailings storage facility - Williams, DJ; King, G (Mine Closure 2016: Proceedings of the 11th International Conference on Mine Closure, 2016)
A completed, conventional, surface slurried coal tailings storage facility in Southeast Queensland, Australia, required capping to facilitate rehabilitation for grazing purposes. The facility had been closed for some years and the upper part of the tailings beach was well-desiccated, while residual ponds covered the low areas with the extent of ponding varying with rainfall. Prior to the commencement of capping, the tailings were tested using a field shear vane, the results of which were used to assess the safe trafficking of the dozer and placement of the initial capping layer. Both the peak and remoulded vane shear strengths were tested, the former representing small-strain loading and the latter representing bow-waving. An initial 1 to 2 m deep capping layer of coarse reject was placed using a D6 Swamp Dozer. Capping commenced from the strongest, highest elevation of the tailings beach, and extended towards the ponds. As the capping progressed, further vane shear testing was carried out to assess the shear strength of the tailings beyond the capping layer, and the strength gain over time in the already covered tailings, which would enable further capping material to be safely placed. The paper describes the capping approach and sequence adopted. The initial capping was followed by the placement of further coarse reject by D9 Dozer.
Keywords: capping